Hemorrhagic Chickenpox - sengupta B; Sarkar J N; Sharma M K; Bhattacharya P; Barman M K (Wolters Kluwer Medknow Publications, 1995)
A case of chickenpox in a boy of 16 years is described for its uncommon presentation with hemorrhagic vesicles, gum-bleeding without being preceded by any prodromal symptom and unassociated with any immunosuppressive disorder.